2020
DOI: 10.1016/j.sapharm.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and characterising multi-compartment compliance aid provision

Abstract: BackgroundMedication compliance aids (MCAs) to support adherence lack evidence for cost-effectiveness yet a 2001 survey in England estimated 100,000 patients receiving an MCA whilst living in their home. Objective(s)To obtain a contemporary estimate of MCA provision by community pharmacies in England and describe factors influencing pharmacist decision-making regarding MCA initiation. MethodsA stratified random sample of two community pharmacies per county (n=40) in England were surveyed by telephone and a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This survey was carried out with hospital Trusts and did not study community services. A study of MCA provision in the community in England has been carried out recently 21 and thus our results, while only capturing hospital services, add to existing knowledge. In addition, our survey has only included Trusts in England, and practice might vary in other parts of the UK.…”
Section: Limitationsmentioning
confidence: 77%
See 1 more Smart Citation
“…This survey was carried out with hospital Trusts and did not study community services. A study of MCA provision in the community in England has been carried out recently 21 and thus our results, while only capturing hospital services, add to existing knowledge. In addition, our survey has only included Trusts in England, and practice might vary in other parts of the UK.…”
Section: Limitationsmentioning
confidence: 77%
“…Free-text responses also showed that some care agencies will only accept the patient if their medication is supplied within an MCA. Care agency request as a main driver for MCA use has been shown in previous research, with acknowledgement that this may be because "carers are not permitted to issue medications to patients (as their company policy)" 21 and that home care workers are required to "have the necessary knowledge and skills" to provide medicines support, 22 which may not be available.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, a review of community pharmacies in England found that most cited a practitioner's judgement of appropriateness as the primary factor informing their decision to give an MCA. Only 16% and 20% respectively reported the patient's or carer's opinion as the key factor 7 . In fact, only 28% of pharmacies carried out a needs assessment at all before commencing use of an MCA, according to a 2019 survey 2 authored by Andre Yeung, a Specialist Pharmacist Advisor and Local Professional Network Chair for Northumberland, Tyne and Wear.…”
Section: Poor Evidence For Multi‐compartment Compliance Aidsmentioning
confidence: 99%
“…Multi-compartment compliance aids (MCAs), commonly known as monitored dosage systems (MDS) or blister packs [ 12 ], have been suggested to improve patient adherence [ 13 , 14 ]. In a recent survey in England, it was estimated that a median of 20 MDS were being prepared by community pharmacies per month [ 15 ], with an estimated 64 million MDS dispensed to around 1.2 million patients in England annually [ 16 ]. However, despite widespread use, there is a lack of evidence of the benefits of MDS [ 17 , 18 ] alongside emerging reports of risk including incidents of patient confusion regarding changing MDS' brands post-hospital discharge [ 19 ].…”
Section: Introductionmentioning
confidence: 99%